Increasing participation by National Health Service knowledge and library services staff in patient and public information: The role of Knowledge for Healthcare, 2014–2019. (31st July 2021) - Carlyle, Ruth; Goswami, Louise; Robertson, Sue
Abstract: Background: The strategy lead for the National Health Service (NHS) knowledge and library services withn the NHS in England is held by Health Education England, working with 184 local NHS libraries based predominantly in hospitals Objectives: As part of the strategic framework Knowkedge for Healthcare, the objective was to increase the role NHS knowledge and library services staff play in both indirect an direct support for evidence‐based information for patients and the public. Methods: The study took an integrated multi‐level approach: encouraging local staff to share their expertise through Task and Finish groups, developing tools, offering training and reviewing levers available through Health Education England's quality assurance role. Results: Between 2014 and 2019, the percentage of services supporting patient and public information increased from 27% to 78%. Qualitative evidence demonstrates a wide range of roles played by local services, working either indirectly or directly to ensure access to evidence‐based health information for patients and the public. Discussion: The study shows the benefits of engaging people with local expertise in developing the skills and resources for system‐wide change. Conclusion: Similar system‐wide change programmes should also consider an integrated approach, involving people, developing tools, offering training and drawing on incentive structures such as quality assurance measures.